Assessment of the Impact of Extension Services on Fish Farming in Ekiti State, Nigeria - F. O, Agbebi (Asian Journal of Agriculture and Rural Development, 2012)
The study was carried out to assess the impact of access to extension services on fish farming in Ekiti State, Nigeria. Specifically, the study investigated the socio – economic characteristics of fish farmers, information disseminated to fish farmers, attributes of extension agents, and farmers’ access to extension services and farmers profitability. A well-structured questionnaire was used to collect information from the farmers and a sample size of 90 fish farmers was selected from the six local government selected. Analysis of data was carried out using frequency and percentage tables and Gross Margin analysis was used to determine the profitability of the farmers. There was relationship between farmers’ access to extension services and their profitability. It was recommended that extension agents should intensify their efforts in reaching farmers and passing useful information to them in order to increase farmers’ profitability.